Rethinking the third place: Could the book cafe be the social interaction catalyst for today's people? - Tastan, Hasan; Polatoglu, Cigdem (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2023)
Third places are gathering places where people spend time in their daily lives between home (first place) and work (second place) and have social interaction with people in the community. As a result of socioeconomic change and technological development over time, third places have changed spatially and socially. This study addresses the types of third places in the literature, focusing on the so-called book cafes, which exhibit both social and functional diversity. The study argues that these places can be called hybrid third place based on the concept of hybrid, which is a biological concept. The study is based on the literature review on third places and the observations made in book cafes, which are places where different functions such as cafe, library, and exhibition space coexist. According to the results of the study, nowadays, new types of third places as well as in-between spaces have emerged. The hybrid third place, designed according to changing needs and socialization practices, is one of them. Considering that today's people's only expectation from the third place is not to have active social interaction with other people, the hybrid third place provides the necessary space for an experience that resembles public space and meets this need. In this context, the characteristics of the hybrid third place as a catalyst for social interaction that brings together people with different social roles were identified. Functional diversity, physical and social accessibility, flexible space design, and historical value of the building are some of them.
Keywords: Book cafe; hybrid third place; social role; socializing; third place; LIFE; Architecture